The impact of psychological distress on quality of care and access to mental health services in cancer survivors - Abdelhadi, Ola (Frontiers in Health Services, 2023)
Introduction Psychological distress is highly prevalent among cancer survivors and significantly impacts their health outcomes. Our study aim is to examine the impact of psychological distress on the quality of care in cancer survivors. Methods We utilized longitudinal panels from the Medical Expenditure Panel Survey data spanning from 2016 to 2019 to estimate the impact of psychological distress on quality of care. We compared a sample of cancer survivors with psychological distress (N = 176) to a matched sample of cancer survivors without psychological distress (N = 2,814). We employed multivariable logistic regression models and Poisson regression models. In all models, we adjusted for age at the survey, sex, race/ethnicity, education, income, insurance, exercise, chronic conditions, body mass index, and smoking status. Descriptive statistics and regression models were performed using STATA software. Results Our findings revealed a higher prevalence of psychological distress among younger survivors, females, individuals with lower incomes, and those with public insurance. Cancer survivors with psychological distress reported more adverse patient experiences compared to those without distress. Specifically, survivors with distress had lower odds of receiving clear explanations of their care (OR: 0.40; 95% CI: 0.17–0.99) and lower odds of feeling respected in expressing their concerns (OR: 0.42; 95% CI: 0.18–0.99) by their healthcare providers. Furthermore, psychological distress was associated with increased healthcare utilization, as evidenced by a higher number of visits (p = 0.02). It also correlated with a decrease in healthcare service ratings (p = 0.01) and the affordability of mental health services (p < 0.01) for cancer survivors. Discussion These findings indicate that psychological distress can significantly impact the delivery of healthcare and the patient experience among cancer survivors. Our study underscores the importance of recognizing and addressing the mental health needs of cancer survivors. It provides insights for healthcare professionals and policymakers to better understand and cater to the mental health needs of this population.